Synthesis and Characterization of Pure and Sn-Doped CeO2 Nanoparticles - Suresh Kumar, K.; Victor Jaya, N. (Asian Journal of Chemistry, 2013)
Nanoporous pure and Sn-doped CeO2 were synthesized via chemical precipitation technique. The structural and optical properties of the prepared ceria nanoparticles were characterized using analytical experimental techniques. X-ray diffraction pattern of the samples shows the formation of single phase cubic structured CeO2 nanoparticles without any secondary impurities. This result was supported by Fourier transform infrared spectroscopy analysis. The porous surface morphology of the nanoparticles was visibly observed from scanning electron microscopy. Optical activity of the samples were measured through UV-visible diffuse reflectance spectroscopy spectrophotometer which shows strong UV absorption band about 300 nm for the pure and doped samples. The extrapolated optical band gap energy values are 4.85 eV and 5.04 eV for the pure and 6 mol % Sn doped CeO2 respectively.